Potential Mechanisms of Progranulin-deficient FTLD - Ward, Michael Emmerson (2011)
Frontotemporal lobar dementia (FTLD) is the most common cause of dementia in patients younger than 60 years of age, and causes progressive neurodegeneration of the frontal and temporal lobes usually accompanied by devastating changes in language or behavior in affected individuals. Mutations in the progranulin (GRN) gene account for a significant fraction of familial FTLD, and in the vast majority of cases, these mutations lead to reduced expression of progranulin via nonsense-mediated mRNA decay. Progranulin is a secreted glycoprotein that regulates a diverse range of cellular functions including cell proliferation, cell migration, and inflammation. Recent fundamental discoveries about progranulin biology, including the findings that sortilin and tumor necrosis factor receptor (TNFR) are high affinity progranulin receptors, are beginning to shed light on the mechanism(s) by which progranulin deficiency causes FTLD. This review will explore how alterations in basic cellular functions due to PGRN deficiency, both intrinsic and extrinsic to neurons, might lead to the development of FTLD.